Vitamin D deficiency in a breastfed child – a case report - Shalihin, Mohd Shaiful Ehsan; Ahmad Zawawi, Muhammad Zul Hazmi (International Journal of Multidisciplinary Research and Publication, 2019)
Vitamin D deficiency in an exclusively breastfed child is increasingly high in prevalence. However it is still not widely reported. Surprisingly, it is still possible for this deficient to occur even in an asymptomatic growing child. Nevertheless, failure to diagnose it earlier, the child can succumb into failure to thrive and developmental delay. Therefore, we would like to share our case report for learning point in primary care assessment for exact detection of features of vitamin D deficiency that almost be missed. This child benefits the prompt detection and treatment of his condition.